The Application of Doctrine of Vicarious Liability to The Hospital in A Event of Medical Personnel Negligence - Rahardianto, Donny; Adriano, Adriano (Soepra Jurnal Hukum Kesehatan, 2024)
The purpose of study were the application of the doctrine of vicarious liability to hospitals in the event of medical personnel negligence. This study used the statute approach and conceptual approach methods. The results of study can be concluded as follows: (1) The basis for the hospital's responsibility for medical personnel negligence can be seen from the aspect of the condition of the therapeutic relationship between the patient and the hospital. If the pattern of therapeutic relationship between the patient and the hospital, then the position of the hospital as the party that provides the achievement, while the doctor only functions as an employee or task executor. With this therapeutic relationship pattern, if there is a patient loss due to medical personnel negligence, then in this case the hospital is responsible. 2) Law Number 44 of 2009 concerning Hospitals was created to provide more certainty in the provision of health services, as well as providing protection for the community and protection for resources in the hospital. The Hospital Law has determined that the hospital will be legally responsible if there is medical personnel negligence that causes losses to the community or patients